Improving the Reach Out and Read Program at a Student-Run Free Clinic for Homeless Women and Children - Kindratt, Tiffany Billmeier; Pagels, Patti; Salinas, Heather; Chung, Kathy; Moehlman, Molly (Journal of Student-Run Clinics, 2017)
Background: We evaluated the Reach Out and Read program in a student-run clinic serving homeless women and children. Objectives were to improve documentation of book delivery and provision of anticipatory guidance in electronic health records (EHRs) and determine changes in student managers’ knowledge, attitudes, and practices towards pediatric literacy. Methods: We evaluated eligible pediatric visits (N=201) and compared the number of books distributed to patients documented on paper to those documented in SOAP notes, which provides a clinic visit summary in EHRs. Student managers received didactic trainings on pediatric literacy, documentation skills, and ways to train volunteers. Student managers were trained to document that a book was provided to the patient, identify which book was provided, and specify that anticipatory guidance about reading was given to the parent in the SOAP note. Student managers were advised to train other student volunteers in this skill. Pediatric literacy knowledge and attitudes were evaluated before and three months after didactic training. Practice behaviors were evaluated after training. SOAP notes were evaluated six months later to determine improvements. Results: Documentation of book delivery in SOAP notes increased (12.5-77.8%) after didactic training (p<0.001). Significant improvements in students’ literacy knowledge were found (p=0.0201). Most students (67%) practiced reading aloud to patients and asked parents to demonstrate reading. After training, all SOAP notes included the name of the book and that anticipatory guidance was provided. Conclusions: Our results emphasize that training can be effective at improving student managers’ knowledge, attitudes, practices, and documentation skills in student-run clinics.